Metabolomic profiles as a new understanding of disease processes - O. Yu. Zolnikova; M. S. Reshetova; M. N. Ivanova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. This review will demonstrate possibilities of using metabolomic profiling to identify biomarkers of various internal organs diseases.Key points. A new diagnostic direction is associated with high-sensitive spectral analysis of biomarker molecules. This review will discuss some of the latest advances with an emphasis on the use of metabolomics to identify major metabolic changes in various diseases. The possibility of finding diagnostic markers in diseases of the gastrointestinal tract, respiratory and cardiovascular systems, in oncology, endocrinology, neurology are discussed. These results define new potential therapeutic strategies, making metabolomics useful for a wide range of biomedical and pharmaceutical research.Conclusion. Metabolomic profile changes in different types of diseases will help to improve understanding of the pathogenesis. New therapeutic approaches may be developed. They will take into account individual characteristics of the patient, identified by using current molecular technologies. The results of metabolomic studies can be used to monitor treatment outcomes.